Ibn Khaldun’s Theory and the Party-Political Edifice of the United Malays National Organisation - bin Syed Jaafar Albar, Syed Hamid (SpringerBriefs in Political Science, 2023)
XIV, 96 p. 6 illus., 3 illus. in color.